Walruses - Murray, Julie, 1969- (2020)
Earth is home to millions of fascinating creatures! Start discovering them with Animal Kingdom. This exciting series explores amazing animal species from all over the world. Each book takes you on a thrilling animal adventure to meet a special creature. Discover what each animal looks like, where it lives, how it survives, and much more.--
Includes index.
Interest grade level: 2-5.
Reading grade level: 3.
Keywords: Walrus -- Juvenile literature; Walruses; Pinnipeds; Walrus; Juvenile works